2015
DOI: 10.1159/000369671
|View full text |Cite
|
Sign up to set email alerts
|

SalA Attenuates Hypoxia-Induced Endothelial Endoplasmic Reticulum Stress and Apoptosis via Down-Regulation of VLDL Receptor Expression

Abstract: Background: Salvianolic acid A (SalA) has been shown to display robust protection against endothelial injury. VLDL receptor (VLDLr) is expressed at high levels in the endothelial cells. However its endothelial biological function has not been completely elucidated. Here, we investigated molecular effects of SalA on endothelial VLDLr expression, ER stress, and apoptosis under hypoxia condition. Methods: Human umbilical vein endothelial cells (HUVECs) pretreated with SalA were subjected to hypoxia stimulation. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Consistent with the findings of previous reports [39] , we demonstrate that the expression of apoptotic biomarkers was substantially increased in lungs of MCT-treated animals. The anti-apoptotic effects of SAA might contribute to inhibition of the development of pulmonary arterial hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the findings of previous reports [39] , we demonstrate that the expression of apoptotic biomarkers was substantially increased in lungs of MCT-treated animals. The anti-apoptotic effects of SAA might contribute to inhibition of the development of pulmonary arterial hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…Apoptosis from lung parenchymal damage has been well recognized in the setting of MCT-induced PAH in recent studies [38,39] . Consistent with the findings of previous reports [39] , we demonstrate that the expression of apoptotic biomarkers was substantially increased in lungs of MCT-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ER proteostasis may be fluctuated by a wide range of stresses, such as glucose deprivation, hypoxia, redox changes and acidosis [5][6][7]. Stresses causing accumulation of unfolded or misfolded proteins drive cell into a condition referred to as ER stress.…”
Section: Endoplasmic Reticulum (Er) Stress and The Unfolded Protein Rmentioning
confidence: 99%
“…We investigated the effect of SFN on ER stess in cardiomyocytes undergoing H/R injury. The ER is an important membranous organelles in all eukaryotic cells, which is extremely sensitive to the stimiulation of ischemia and hypoxia [28] . Studies have shown that ER stress is a pivotal pathophysiological mechanism of myocardial ischemia reperfusion (I/R) injury [29][30][31] .…”
Section: Wwwchinapharcom LI Yp Et Almentioning
confidence: 99%